Territorial governance: the concept, the approaches the principles - El Bazoui, Jaouad (Journal of Humanities & Social Sciences, 2019)
The topic of territorial governance is considered a topic of paramount importance that has gained the interest of modern societies as it is the perfect framework to crystallize a new strategy capable of building a good societal development which its texture is governance and sustainability. Therefore, it has become the main concern of researchers to find a way for the crises and the failures that international organizations, countries, companies and public administrations know.However; the use of this term is frequently surrounded by mystery and ambiguity in terms of the date of its inception its development and the determination of its meaning ,perhaps that is one of the methodological problems that faces social sciences; for usually it is difficult to give a unified inclusive ,definition to a specific concept; nevertheless, this doesn’t’ t prevent the structured search and attempting to access its roots to grasp its meanings and purposes ;what is more territorial governance isn’t an abstract idea or a logo raised for consumption. But it is an integrated system that requires the availability and the interaction of a set of foundations and elements, which didn’t have a background or unified objectives.Accordingly we will try to treat this problem beginning by determining the concept of territorial governance on the one hand and we will stand at its important approaches and principles on the other hand.
Keywords: governance; soil; territorial governance; development; human development